Apatía a la práctica del matrimonio eclesiástico de los jóvenes entre los 18 y 35 años del cantón Chambo de le diócesis de Riobamba durante el periodo 2010-2014 - Sayago Gahui, Justo Benjamín (2014)
This research attempts to describe the situation that is going through the sacrament of marriage by apathy that have developed youth in recent unquestionable years example of this are: divorces, separations, with experience in union both urban sectors rural; As in the canton Chambo where couples living this reality.